Persistent Neuroadaptations in the Expression of Genes Involved in Cholesterol Homeostasis Induced by Chronic, Voluntary Alcohol Intake in Rats - Alsebaaly, Josette; Dugast, Emilie; Favot, Laure; Rabbaa Khabbaz, Lydia; Solinas, Marcello; Thiriet, Nathalie (Frontiers in Molecular Neuroscience, 2018)
Alcohol use disorder is associated with persistent adaptations in the brain that are believed to participate in the long-lasting vulnerability to relapse after abstinence. Cholesterol, the major sterol compound found in the central nervous system, plays a major role in maintenance of neuronal morphology, synaptogenesis and synaptic communication and may be involved in alcohol-induced neuroadaptations. In this study, we investigated whether alcohol consumption in a two-bottle choice paradigm followed by 3 weeks of abstinence could alter the expression of genes encoding proteins involved in cholesterol homeostasis in brain regions involved in addiction and relapse, namely the prefrontal cortex (PFC), the nucleus accumbens (NAc), the mesencephalon and the amygdala. We found that voluntary alcohol intake followed by 3 weeks of forced abstinence produces changes in the transcription of several genes encoding proteins directly involved in cholesterol synthesis such as HMGcoA reductase, FDFT1 and FDPS and in its regulation such as SREBF2, in cholesterol transport such as ABCA1 and in cholesterol degradation such as CYP46A1. Interestingly, these changes appeared to be region-specific and suggest that previous chronic exposure to alcohol might durably increase cholesterol metabolism in the PFC, the NAc and the mesencephalon and decrease cholesterol metabolism in the amygdala. Altogether, these results suggest that alcohol consumption leads to durable deregulations in cholesterol metabolism in key areas involved in loss of control over drug use and addiction. These long-term neuroadaptations may participate in the changes in brain structure and functioning that are responsible for the long-lasting risks of relapse to alcohol.